ANALISIS REGULASI EMOSI NEGATIF SISWA LAKI-LAKI - Harmalis Harmalis; Farid Imam Kholidin; Inggrid Portuna Ningsih (Indonesian Journal of Counseling and Development, 2023)
When entering adolescence, individuals experience several psychological and physiological changes. One of the psychological changes that occur during adolescence is socio-emotional change, where adolescents have relatively high emotional tension, such as several incidents of disputes and fights between students, which indicates a lack of ability to regulate and control the negative emotions that exist in them. This study aims to describe the ability of male students at MTs Siulak Gedang to regulate negative emotions. Quantitative research with a descriptive quantitative approach was chosen for this study, and questionnaires were used to obtain information from the respondents. The results obtained are generally seen from the acquisition of the average indicator score: (1) Able to manage positive and negative emotions, where this indicator obtains an average value of 2.95, which means it is included in the high category; (2) Able to realize and control emotions automatically, this indicator also obtains an average value that is also included in the high category, which is equal to 2.96, and in the last indicator (3) Being able to deal with stress from problems encountered also obtains high results, where in this indicator students get the average value of 3.04.